2018
DOI: 10.1016/j.eurpsy.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Functioning mediates help-seeking for mental problems in the general population

Abstract: Our cross-sectional data indicate a gap in help-seeking for mental problems/disorders. The relationship between number of mental problems/disorders and help-seeking mediated by functional impairment confirm that individuals commonly do not seek help until problems are severe enough to cause problems in occupational and psychosocial functioning, driving the already immense costs of mental disorders. Thus, campaigns promoting early help-seeking, including early diagnostic clarification of and support for subthre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 65 publications
(88 reference statements)
8
28
1
1
Order By: Relevance
“…Treatment gap varied across disorders; alcohol dependence had the highest treatment gap (97%), while the lowest treatment gap was observed among those with GAD (62.1%). Similar differences have been reported in other studies [19,20]. Several factors could have contributed to the high gap observed amongst those with alcohol dependence.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Treatment gap varied across disorders; alcohol dependence had the highest treatment gap (97%), while the lowest treatment gap was observed among those with GAD (62.1%). Similar differences have been reported in other studies [19,20]. Several factors could have contributed to the high gap observed amongst those with alcohol dependence.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent study by Font et al [19], lifetime treatment gap was found to be positively associated with being male and practicing religion, and negatively associated with aging, being single, being a French native (versus other nationalities) and experiencing a mood, anxiety, alcohol or substance use and psychotic disorder (versus those not having any disorder). In contrast, a study by Michel et al [20] that examined current help-seeking found that functional impairment and presence of an affective disorder were associated with the highest odds of help-seeking. Other sociodemographic variables, such as age and gender, were unrelated to current help-seeking.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Overall level of functioning, as indexed by the SOFAS score, were similar to the functioning level of nonhelp-seeking adolescent samples from other countries [29,35]. The SOFAS score in our sample was mostly affected by the severity of CAARMS symptoms; therefore, not surprisingly, the ARMS + group had poorer functioning than the ARMS-group.…”
Section: Discussionsupporting
confidence: 69%